2019
DOI: 10.1016/j.tiv.2019.104623
|View full text |Cite
|
Sign up to set email alerts
|

Capacity of an in vitro rat skin model to predict human dermal absorption: Influences of aging and anatomical site

Abstract: In addition to inhalation, dermal absorption is a route of exposure to be considered when assessing occupational risks. To investigate dermal penetration of chemicals, human skin samples are regarded as the gold standard. As human samples can be difficult to obtain, many experiments are performed with rat skins, and the results extrapolated to describe human percutaneous absorption. Here, we examined the characteristics of rat skin samples and compared absorption to that measured with in vitro human skin. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…4 The treatment parameters of the 405-/635-nm dual-diode laser in our experimental study were determined according to the previous clinical reports. 4,18 The simultaneously activated wavelengths of 405 nm at a power of 24 mW and 635 nm at 18 mW for 12 min have been known to be unaffecting temperature changes in treated areas. 4 In our study, the 405-/635-nm dual-diode laser treatment in guinea pigs with dermatophytosis achieved 87.5% negative conversion of mycologic studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 The treatment parameters of the 405-/635-nm dual-diode laser in our experimental study were determined according to the previous clinical reports. 4,18 The simultaneously activated wavelengths of 405 nm at a power of 24 mW and 635 nm at 18 mW for 12 min have been known to be unaffecting temperature changes in treated areas. 4 In our study, the 405-/635-nm dual-diode laser treatment in guinea pigs with dermatophytosis achieved 87.5% negative conversion of mycologic studies.…”
Section: Discussionmentioning
confidence: 99%
“…This study used guinea pigs to develop an in vivo animal model of dermatophytosis because their skin shares many structural similarities with human skin. 18 Then, the skin of guinea pigs was infected with mixed preparation of T. rubrum and T. mentagrophytes suspensions to reduce the number of enrolled experimental animals. Mycological studies using scraped samples after completing six sessions of dual-diode laser treatment in the infected guinea pig groups revealed that seven of eight (87.5%) samples in each group had negative results in direct KOH microscopy and fungal culture studies.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on the efficacy of iNs obtained by this method in treating animal models of neurodegenerative diseases, such as AD and PD, are needed. In addition, although there are few genetic similarities between Homo sapiens and Rattus norvegicus, rat cells are widely used in experiments to provide a foundation for human research. However, rats and humans are different species, so whether this method has good efficacy when applied to human cells needs to be verified in future experiments.…”
Section: Discussionmentioning
confidence: 99%
“…Rat skin was taken for the study although there is different rate of absorption of drugs as compare to human skin but we can compute and correlate it with human skin permeation and absorption 36 . Franz diffusion cells having diffusion area 0.785 cm 2 of 10 mL volume of receptor were used to measure the rate of skin penetration.…”
Section: Methodsmentioning
confidence: 99%